Keyboard-less System Using EEG Signals - Mohamed, Azza Hashim (IRC, 2016)
This project is aimed to design a system which is keyboard less and replaces the conventional keyboards that have been used over the past two centuries. Due to their intensive use in today’s environment, it is necessary to keep them up-to-date with the technology. This need becomes critical for paralyzed people since the use of conventional keyboard is impossible. The goal of this project is to correctly detect the 10 digits (0 to 9) with the possibility to extend it towards all the alphabets in future. It can then be named as keypad-less system which is capable to be used with other external devices to input the desired number. The main outcome of this project is the development of an intelligent computer interface application which investigates the decision making area of the brain.